Regulasi Diri dalam Belajar pada Mahasiswi Multi Peran (Ibu Menyusui) - Qalbi, Laode Surazal; Puri, Valendra Granitha Shandika (Universitas Muhammadiyah Purwokerto, 2023)
This study was conducted to find out and understand more about self-regulated learning in students who have multiple roles (as housewives and nursing mothers) with good learning performance. Researchers use a qualitative-phenomenological approach to reveal this phenomenon. The research subjects were selected by purposive sampling technique and the data collection technique used was in-depth interviews. The results of this study found that 3 subjects used self-regulation learning in the form of cognitive regulation, motivation regulation, behavior regulation, and emotional regulation. In addition, the subjects also tried to optimize context regulation even though it was not optimal so their learning objectives could be achieved. Self-regulation in learning carried out by the subjects is influenced by several triggering factors and the characteristics of each individual. Social support from family and friends obtained is also considered very helpful for the subjects in the success of their learning regulation.